High salt stress in Bacillus subtilis: involvement of PBP4* as a peptidoglycan hydrolase - Palomino, Maria Mercedes (2009)
The study was focused on the role of the penicillin binding protein PBP4* of Bacillus subtilis during growth in high salinity rich media. Using pbpE-lacZ fusion, we found that transcription of the pbpE gene is induced in stationary phase and by increased salinity. This increase was also corroborated at the translation level for PBP4* by western blot. Furthermore, we showed that a strain harboring gene disruption in the structural gene (pbpE) for the PBP4* endopeptidase resulted in a salt-sensitive phenotype and increased sensitivity to cell envelope active antibiotics (vancomycin, penicillin and bacitracin). Since the pbpE gene seems to be part of a two-gene operon with racX, a racX::pRV300 mutant was obtained. This mutant behaved like the wild-type strain with respect to high salt. Electron microscopy showed that high salt and mutation of pbpE resulted in cell wall defects. Whole cells or purified peptidoglycan from WT cultures grown in high salt medium showed increased autolysis and susceptibility to mutanolysin. We demonstrate through zymogram analysis that PBP4* has murein hydrolyze activity. All these results support the hypothesis that peptidoglycan is modified in response to high salt and that PBP4* contributes to this modification. © 2008 Elsevier Masson SAS. All rights reserved.